Unusual prosthetic femoral head fracture in total hip arthroplasty: ceramic on polyethylene articulation. (10th February 2014) - Tucker, Damien; Acharya, Mehool
Abstract : A 68-year-old man with a previous right total hip arthroplasty presented with acute pain in the right hip, and no associated trauma was reported. The previous hybrid arthroplasty consisted of a ceramic femoral head articulating on an ultra-high-molecular-weight polyethylene liner. The unusual diagnosis of fractured ceramic femoral head was made and an urgent revision arthroplasty was performed to remove the ceramic bearing as well as all implants that may have come into contact with the ceramic. This case report highlights the material properties of ceramics in total hip arthroplasties as well as the importance of regular follow-up in these patients.